2017
DOI: 10.1039/c6fd00230g
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale QM/MM calculations of the CaMn4O5 cluster in the S3 state of the oxygen evolving complex of photosystem II. Comparison between water-inserted and no water-inserted structures

Abstract: Large-scale QM/MM calculations were performed to elucidate an optimized geometrical structure of a CaMnO cluster with and without water insertion in the S state of the oxygen evolving complex (OEC) of photosystem II (PSII). The left (L)-opened structure was found to be stable under the assumption of no hydroxide anion insertion in the S state, whereas the right (R)-opened structure became more stable if one water molecule is inserted to the MnCa cluster. The optimized Mn-Mn distance determined by QM/MM was abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Previous and new SFX structures for the S 3 state of OEC of PSII provided structural information for elucidation of scope and applicability of the QM/MM results (Shoji et al , , ). The Mn‐peroxide with a short O (5) ‐O (6) distance (1.5 Å) was compatible with the SFX structure by Okayama group (Suga et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous and new SFX structures for the S 3 state of OEC of PSII provided structural information for elucidation of scope and applicability of the QM/MM results (Shoji et al , , ). The Mn‐peroxide with a short O (5) ‐O (6) distance (1.5 Å) was compatible with the SFX structure by Okayama group (Suga et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Fig. A,B show variations of the optimized geometrical structures by QM/MM at the S 2 to S 3 transition (Shoji et al , 2018), where the yellow and red colors are used for the R‐opened S 2 (4443) and S 3 (4444) structures, respectively. From Fig.…”
Section: Displacements Of Glu189 With Water Insertion In the S3 Statementioning
confidence: 99%
See 1 more Smart Citation
“…17,5559 Results from structural biology on the oxygen evolving complex (OEC) suggest that H-bonding networks to coordinate water molecules assist in forming Mn–OH complexes that can be in either the Mn III or Mn IV oxidation states. 6064 One approach toward studying the structural outcomes of the secondary coordination sphere is to develop chelating ligands that can provide H-bond donors/accepts around the Mn–OH unit. Toward this goal, tripodal ligand [H 2 pout] 3- was designed to accommodate three intramolecular H-bond to the hydroxido ligand.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] Computational studies also revealed the presence of intermediate states within the catalytic cycle of PSII, which suggested the presence of different isomers representative of the S 1 , [23,24] S 2 [24][25][26] and S 3 states. [24,[27][28][29][30] In particular, for the S 3 state, experimental evidence demonstrates that the Mn 4 Ca cluster is arrangedi nao pen cubane fashion, [31] with the possible presence of an additional hydroxyl group bound to the Mn1 ion. [15] This conformation is also suggested by computational studies, which additionally support the presence of ah ydroxyl group bound to the Mn1 ion (see also Figure 1).…”
Section: Introductionmentioning
confidence: 99%